1987
DOI: 10.1017/s0021859600081673
|View full text |Cite
|
Sign up to set email alerts
|

The digestion, by sheep, of diets containing different physical forms of rapeseed

Abstract: SummaryThe effect of including full-fat rapeseed (Brassica napus, cv. Jet Neuf) into diets for mature wether sheep was studied. A 4 × 4 latin square was carried out with diets containing 4% rapeseed oil in different physical forms: as intact seeds; as a mixture of rapeseed oil and rapeseed meal; or as an extruded rapeseed product. A control diet, containing rapeseed meal but no added oil, was also fed.There was no effect of added oil on rumen fermentation or dietary fibre digestibility. Extrusion had the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…Only a few comparisons between seeds and oils have been published. Pallister and Smithard (1987) reported a trend toward a lesser ruminal OM digestibility with extruded rapeseed than with crude rapeseed or rapeseed oil, as observed in our study for fiber digestibility with ELS compared with CLS and LSO (P = 0.11). Had we used more animals in our study, we might have detected the small differences among linseed treatments.…”
Section: Diet Digestibilitysupporting
confidence: 84%
“…Only a few comparisons between seeds and oils have been published. Pallister and Smithard (1987) reported a trend toward a lesser ruminal OM digestibility with extruded rapeseed than with crude rapeseed or rapeseed oil, as observed in our study for fiber digestibility with ELS compared with CLS and LSO (P = 0.11). Had we used more animals in our study, we might have detected the small differences among linseed treatments.…”
Section: Diet Digestibilitysupporting
confidence: 84%
“…In addition, Gonthier et al (2004) and Martin et al (2008) with linseeds, Ferlay et al (1992); Albro et al (1993) and Petit et al (1997) with soybeans or rapeseeds, did not find any effect of extrusion on forestomach and total tract OM or fibre digestibility. Likewise, with oil and whole seeds, Pallister and Smithard (1987) did not find differences in digestion of rapeseed oil versus oil included in rapeseeds while, more recently, Martin et al (2008) did not find differences between linseed oil and oil included in linseeds.…”
Section: Digestibility and Ruminal Digestionmentioning
confidence: 93%
“…For instance, milk yield and composition were optimized when Jet-Sploded whole canola seed was included at 4.5% of the diet but were diminished at higher levels (up to 17.4%; Khorasani et al, 1991). Pallister and Smithard (1987) indicated that sheep fed 4% extruded whole rapeseed had lower OM, N, and fiber digestibilities than sheep fed untreated whole seed, yet less 18:1 was biohydrogenated in the rumen and small intestinal digestibility of 18:1 increased by 15% when sheep were fed the extruded rapeseed. suggested some protection of unsaturated fatty acids by extrusion of rapeseed, because they were able to include rapeseed at up to 14% of the DM of a hay-based diet fed to cows without adversely affecting fiber digestibility.…”
Section: Canola Seed Dietsmentioning
confidence: 99%